2019
DOI: 10.1002/dc.24311
|View full text |Cite
|
Sign up to set email alerts
|

Value of combined use of fine‐needle aspiration and core needle biopsy in palpable breast tumors performed by pathologist: Institut Curie experience

Abstract: The aim of this study was to determine the accuracy of fine-needle aspiration (FNA) and core needle biopsy (CNB) for palpable breast tumors (PBTs). FNA and CNB of 492 PBTs from 477 patients were analyzed. Tumors were malignant in 473 cases and benign in 19 cases. There was a strong correlation (P > .05) between FNA and CNB in terms of malignancy. Among 473 malignant tumors, FNA had better accuracy and less unsatisfactory results (95.6%; 2.7%) than CNB (94.9%; 4.9%). Among 19 benign tumors, CNB was accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(46 reference statements)
1
12
2
Order By: Relevance
“…The 3×2 cell matrix summarizes all the data observed including suspect results, giving more characteristics to the diagnostic test such as Y + , Y − and LR ±. Note that the S e c and S p e c obtained when we only handled the suspect results, applying the conditional 3×2 cell matrix proposed by Simel et al [ 16 ], were close to those obtained by Sustova et al [ 4 ]. However, verification bias had to be handled too.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The 3×2 cell matrix summarizes all the data observed including suspect results, giving more characteristics to the diagnostic test such as Y + , Y − and LR ±. Note that the S e c and S p e c obtained when we only handled the suspect results, applying the conditional 3×2 cell matrix proposed by Simel et al [ 16 ], were close to those obtained by Sustova et al [ 4 ]. However, verification bias had to be handled too.…”
Section: Discussionsupporting
confidence: 74%
“…When diagnosing breast tumors, the Fine Needle Aspiration Cytology (FNAC) test is widely used [ 4 ]. It has been reported as a simple, minimally invasive, and cost-effective technique for the diagnosis of breast cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we continue to recommend FNAB for the evaluation of breast masses, especially in a low-risk setting like BIRADS 4a tumors. Other studies have found comparable performance for FNAB compared to CNB in palpable breast tumors [19].…”
Section: Discussionmentioning
confidence: 94%
“…Even though core‐needle biopsies are recommended for a confirmatory diagnosis of breast cancer, 15 we believe that FNAB still should play an important role in the diagnosis of breast lesions 16 . Core‐needle biopsies provide the ability to document invasion and conveniently provide tissue for assessment of estrogen receptor, Progesterone receptor, and HER2 positivity in the invasive component in malignant lesions, 17 but FNAB provides a few advantages when assessing benign lesions.…”
Section: Discussionmentioning
confidence: 99%